Kinetics of ABE fermentation considering the different phenotypes present in a batch culture of Clostridium beijerinckii NCIMB-8052 - Paredes, Ivan; Quintero, Julian; Guerrero, Karlo; Gallardo Marusich, Roberto Andres; Mau, Silvia; Conejeros, Raul; Carlos Gentina, Juan; Aroca, German (My University, 2022)
Background: In solvent-producing Clostridium species, several physiological conditions and morphological forms can be observed during batch ABE fermentation. Currently, the contribution made by each condition or form to the production of acids and solvents is not clear. Flow cytometry and fluorescence microscopy have been used to analyze the presence of different morphological and physiological conditions for Clostridium species; however, there are few studies to quantify their contribution to fermentation kinetics. Results: Morphological changes of the batch cultures of Clostridium beijerinckii NCIMB-8052 were followed by flow cytometry and epifluorescence microscopy. Three cell types were identified, and the percentage of each one was estimated along the culture, showing that they are present throughout the culture and its population distribution was in agreement with the kinetics of growth and acids and solvents production. Yields for the global population and for each subpopulation were estimated. The values of the yield for butanol and acetone based on the fraction of solventogenic cells were 2.5 times the values of the parameters obtained for the whole biomass, while those for acetic and butyric acids based on the acidogenic cell type was 1.5 times. Conclusions: Quantitative analysis of the subpopulations by flow cytometry allows the calculation of the yields related to specific cell types, isolating the contribution of each subpopulation to the production of acids and solvents. How to cite: Paredes I, Quintero J, Guerrero K, et al. Kinetics of ABE fermentation considering the different phenotypes present in a batch culture of Clostridium beijerinckii NCIMB-8052. Electron J Biotechnol 2022;56. https://doi.org/10.1016/j.ejbt.2021.12.002 (c) 2022 Pontificia Universidad Catolica de Valparaiso. Production and hosting by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: abe fermentation; acidogenic; batch cultures; butanol production; clostridium; clostridium beijerinckii; fermentation kinetics; flow cytometry; fluorescence microscopy; solventogenic; solvents production